Fenomena Gejala Pilek paling Sering pada Pasien COVID-19 - Joekly Wahidan Muharaam; Diana Samara (Jurnal Biomedika dan Kesehatan, 2022)
BackgroundCOVID-19 is an infectious disease caused by SARS-CoV-2, a new coronavirus that has never been identified in humans that causes various symptoms. Symptoms of COVID-19 that are quite often found are cough, runny nose, fever. Antigen rapid test is an examination with high sensitivity and specificity, often used in COVID-19 detection. This study aims to determine the relationship between cough, cold, and fever symptoms with positive results of COVID-19 antigen rapid test. MethodsThis study used cross-sectional design using medical records. The variables assessed were cough, cold, fever, and the results of COVID-19 antigen rapid test. Data analysis was performed using chisquare test and logistic regression test with significance level of p<0.05. ResultsSubject are mostly are 31-45 years old and female. Subjects had symptoms of cough (88.2%), fever (80%), and runny nose (60%). The results of the COVID-19 rapid test antigen were found to be more reactive (80%). The distribution of reactive results of the COVID-19 rapid antigen test was 86.7% in cough, 92.2% in colds, and 91.2% in fever. There was a significant relationship between cough (p=0.000), runny nose (p=0.001), and fever (p=0.000) with reactive results of the COVID-19 rapid test antigen. Patients with cold symptoms have an 8.67 times greater risk of reactive COVID-19 antigen rapid tests. ConclusionsThere is a relationship between symptoms of cough, runny nose, and fever with reactive results in patients aged 17 years and over. Complaints of a cold have a higher risk of reactive results on the COVID-19 rapid test antigen examination compared to cough and fever. This means that patients with colds need to be more aware of being infected with COVID-19.